The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jpcc.8b00467
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Ways To Bend and Break Reaction Pathways Using Mechanochemistry

Abstract: Mechanical forces can lead to qualitative changes in reaction mechanism, which depend on the specific mode of force induction and inherent chemistries of the mechanophore. To demonstrate these effects at an atomistic level, three challenging mechanochemical transformations of recent interest are herein studied: spiropyran ring opening, flex-activated small molecule release, and cyclopropane ring opening. These examples show that mechanical load can eliminate intermediates and transition states along a reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Other computational studies have suggested that this reaction manifold is less sensitive to external mechanical perturbation and that a significant thermal component is still required for activation under relatively large forces. 20 Poor orientational alignment between the scissile bonds and the direction of applied force along the reaction coordinate results in weak mechanochemical coupling in these systems, and mechanical force alone is insufficient for activation. The formal retro-Diels−Alder reaction of phenyltriazolinedione−anthracene adduct 34 was also investigated experimentally in cross-linked elastomers under tension where mechanical activation is expected to proceed via force-induced planarization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Other computational studies have suggested that this reaction manifold is less sensitive to external mechanical perturbation and that a significant thermal component is still required for activation under relatively large forces. 20 Poor orientational alignment between the scissile bonds and the direction of applied force along the reaction coordinate results in weak mechanochemical coupling in these systems, and mechanical force alone is insufficient for activation. The formal retro-Diels−Alder reaction of phenyltriazolinedione−anthracene adduct 34 was also investigated experimentally in cross-linked elastomers under tension where mechanical activation is expected to proceed via force-induced planarization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Roessler and Zimmerman used the growing string method (GSM) without using the θ value as a constraint coordinate and showed that the reaction mechanism for the flex activation depended on the applied force. 95 The activation energy decreased mostly linearly with increasing force and was approximately 24 kcal mol −1 if 4 nN of force were applied relative to the ground state reaction. Transition states calculated with different applied forces showed unique θ values, indicating that the reaction followed a multiparameter pathway and force influenced only one reaction coordinate.…”
Section: Flex Activation Of [4 + 2] Cycloadductsmentioning
confidence: 96%
“…Roessler and Zimmerman previously used GSM computations to locate reaction paths and products for SP1. 95 In their study, they identified two merocyanine products, the Z-and E-isomer (Scheme 34). At forces <2 nN the Z-product was found, but at higher forces the ring-open structure isomerized to the E-structure without an energy barrier.…”
Section: Polymer Chemistry Reviewmentioning
confidence: 99%
“…26,27 Computational studies have established that the unique reactivity of mechanophores originates from a distortion of the potential energy surface under large forces, which fundamentally changes the reaction landscape and leads to different reaction pathways. [28][29][30]…”
Section: Synpacts Syn Lettmentioning
confidence: 99%